Criteria for evaluation of response to biologics in severe asthma – the Biologics Asthma Response Score (BARS) - Milger, Katrin; Korn, Stephanie; Feder, Claudia; Fuge, Jan; Mühle, Andreas; Schütte, Wolfgang; Skowasch, Dirk; Timmermann, Hartmut; Suhling, Hendrik (Pneumologie, 2023)
Background The introduction of monoclonal antibodies (biologics) has revolutionized the therapy of severe asthma. Even though there is a response in the majority of patients, the degree of response varies. To date criteria for assessment of response to biologics are not consistently defined.Aim To define criteria for evaluation of response to biologics that are precise, simple and suitable for daily use in order to guide decision-making regarding continuation, switching or stopping of biological therapy.Methods 8 physicians with large experience in this indication, supported by a data-scientist, developed a consensus on criteria to evaluate response to biologics in patients with severe asthma.Result We developed a combined score based on current literature, own experience and practicability. It uses the main criteria exacerbations, oral corticosteroid (OCS) therapy and asthma control (asthma control test, ACT). We defined thresholds for “good response”, “response” and “insufficient response” rated with a score of “2”, “1” and “0” respectively: annual exacerbations (“0 or reduction ≥ 75 %”, “reduction 50–74 %”, “reductio < 50 %”), daily OCS dose (“stopping or reduction ≥ 75 %”, “reduction 50–74 %”, “reduction < 50 %”), asthma control (“ACT increase ≥ 6 or ≥ 3 with result ≥ 20”, “ACT increase 3–5 with result < 20”, “ACT increase < 3”). Additional individual criteria like lung function and comorbidities may be important for evaluation of response. We propose 3, 6 and 12 months timepoint for assessment of tolerability and response. Using the combined score, we developed a scheme to guide the decision whether switching the biologic should be considered.Conclusion The Biologic Asthma Response Score (BARS) serves as objective and simple tool to evaluate response to biologic therapy using the three main criteria exacerbations, OCS use and asthma control. A validation of the score was initiated.
Keywords: severe asthma; biologics; response; criteria; score; switching